Poetics, Ideology, Dissent Beppe Fenoglio and Translation - Vetri, Valentina (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book examines the translations carried out by Italian novelist Beppe Fenoglio, one of the most important Italian writers of the twentieth century. It stems from the acknowledgement that Beppe Fenoglio's translations have not been examined in the political, cultural and ideological context in which they were produced, but have been dismissed as a purely linguistic exercise. The author examines Fenoglio's translations as culturally and ideologically informed artistic expressions, in which Fenoglio was able to give voice to his dissent towards the mainstream ideology and poetics of his times, often choosing authors and characters with whom he identified, such as Shakespeare, Milton and Marlowe. The interaction between the theories of Translation Studies, Literary Theory and Adaptation Studies foregrounds the centrality of the role of the translator, showing how Fenoglio's ideology and poetics were clearly visible both in the selection of the texts he translated and in his translation strategies. Valentina Vetri is Adjunct Professor in English Language and Translation at the University of Siena, Italy.
CHAPTER 1. INTRODUCTION -- CHAPTER 2. "A PRIVATE AFFAIR": THE CRITICAL RESPONSE TO FENOGLIO'S TRANSLATIONS AND NEW PERSPECTIVES FROM TRANSLATION STUDIES -- CHAPTER 3. CHALLENGING EDUCATION AND CULTURE IN FASCIST ITALY: HOW FENOGLIO BECAME A TRANSLATOR -- CHAPTER 4. A PREDILECTION FOR DISSENTING HEROES: FENOGLIO'S TRANSLATIONS OF CRISTOPHER MARLOWE'S DR FAUSTUS AND JOHN MILTON'S SAMSON AGONISTES -- CHAPTER 5. "FALSTAFFIAN" PARTISANS: FENOGLIO'S TRANSLATION OF SHAKESPEARE'S Henry IV Part 1 AND FENOGLIO'S ORIGINAL WRITINGS -- CHAPTER 6. TWO CIVIL WARS COMPARED: FENOGLIO'S TRANSLATION OF CHARLES FIRTH'S OLIVER CROMWELL AND THE RULE OF PURITANS IN ENGLAND -- CHAPTER 7. THE FINE LINE BETWEEN TRANSLATION AND ADAPTATION: FENOGLIO'S LA VOCE NELLA TEMPESTA AND THE TRANSLATION OF GARROD'S INTRODUCTION TO WUTHERING HEIGHTS -- CHAPTER 8. CONCLUSION.
Keywords: Translating and interpreting; European literature; Comparative literature; Literature -- Philosophy; Adaptation (Literary, artistic, etc.).; Language Translation; European Literature; Comparative Literature; Literary Theory; Adaptation Studies